Wild bread : flour + water + air : sourdough reinvented - Butters, MaryJane, 1953- (Gibbs Smith, 2018)
Until now, sourdough was perceived as too much work. In Wild Bread, the author (owner of the 1890 historic Barron Flour Mill in Oakesdale, Washington) presents a quick and easy 1 minute 2x/day technique, and demonstrates the use of eight different types of flours for each bread featured--everything from gluten-free brown-rice flour to quinoa to common white to heirloom whole wheat--for a whopping 295 recipes and 475 photographs.